A Financial Appraisal of Business Improvement Districts in the UK. (August 2014) - Hemphill, Lesley; Berry, Jim; McGreal, Stanley
Urban regeneration has increasingly emphasised long-term policy objectives and public—private partnership arrangements where risk and profits are more equitably distributed between the parties. Similarly, successive governments have endorsed area-based regeneration vehicles with increasing importance placed on enterprise zones, business improvement districts (BIDs), tax incremental finance, and other local asset backed vehicles. Each regeneration vehicle necessitates a clear policy direction and performance measurement of its policy outputs to ensure that funding is targeted at initiatives delivering sustainability impacts. This paper presents a 'market' and 'nonmarket' appraisal of the financial impact of BIDs as an area-based regeneration vehicle. It utilises data from a UK-wide survey to demonstrate the potential of BIDs in generating direct income and indirect investment and how the output capacity of the BID model increases over time. The paper concludes that BIDs have significant leverage potential whilst acting as a key conduit for coordinating wider area-based regeneration.